Importance of Indications of Deviations for Preventing Incidents at Seveso Sites - Henk J. Manuel; Mark P.N. Spruijt; Jochem H.J. Wijtten; Bert G. Wolting (Chemical Engineering Transactions)
Incidents over the past 20 years at Seveso sites in the Netherlands have been analysed with the Storybuilder MHCA (major hazard chemical accidents) model. The model assumes that deviations from process control barriers can be used to bring the process back to a safe envelope. For this, deviations need to be indicated (I), detected (D), diagnosed (D) and responded (R) to: the "IDDR" framework. This framework helps in determining how deviations were handled in incidents, which influencing factors played a role and how they were connected to flaws in the safety management system. Analysis of 375 incidents shows that in half the cases studied deviations were not properly indicated, either due to missing equipment or procedures or simply being inadequate, not fit for purpose. Influencing factors that can be used to improve on indicating deviations are given in this paper: periodic inspections and review of hazard assessments, leak testing, monitoring of process parameters and last minute risk assessment. Flaws in the safety management system can lead to deviations and the paper provides some thoughts on possible improvements with respect to the elements of operation control, management of change and identification and evaluation of major hazards. The paper gives a number of examples of incidents for clarification of elements of the model and helps with learning from incidents.